Caracterização mineralógica e propriedades eletrocinéticas de hematitas do Quadrilátero Ferrífero - Andréia Bicalho Henriques (2009)
The metal oxides and hydroxides, such as iron oxides, become charged when dispersed in water. Changes in the oxides surface and the formation of interface between the electrically charged particles and water are controlled by pH and ionic strength of the solution they are dispersed in. Aiming to better understand the zeta potential in samples of hematite with different morphologies and textures it is intended in this work: to characterize mineralogically compact, specular and porous hematite, from the Iron Quadrangle; and to measure comparatively their electrokinetic properties. Evaluating the systems studied and the electrokinetic behavior of hematite particles, it was possible to identify ionic species that are engaged in fundamental control of the mineral surface charge and surface potential of a dispersed phase as the ions H+ and OH-, which are the potential determining ions in the system. The ionic species used as indifferent electrolyte had the function of controlling the extent of the diffuse double layer, not being involved in specific interactions with the surface. The main crystalline phase identified by XRD in the samples was the hematite mineral phase. However, the hematite samples present contaminants: compact hematite has quartz in low content, specular hematite sample contains other silicates (kaolinite and muscovite) also in low occurrence and porous hematite sample has gibbsite also in low content. The porous hematite showed greater surface specific area (2.327m2/g), due to the presence of a larger volume of pores, the measured surface area of the compact hematite sample was 1.604m2/g and for the specular hematite sample was 0.617m2/g.The determined isoelectric points approaching the values cited in literature were those determined by the microeletroforesis technique, by zeta potential measurement. The electrolytes with the nitrate ions were more appropriate than the electrolytes with chloride ions regarding hematite: -sodium nitrate by the technique of electrophoresis: porous hematite showed value of isoelectric point (IEP) at pH 6.5, the compact and specular hematite showed lower values of IEP (pH 6.2 and 6.3, respectively); -potassium nitrate by the technique of electrophoresis: compact hematite showed value of isoelectric point (IEP) at pH 6.1, the compact and specular hematite showed IEP pH values of 6.0 for both;-sodium nitrate by the method of Mular and Roberts: compact hematite showed value of isoelectric point (IEP) at pH 6.7, specular hematite at pH = 6.8 and porous hematite presented IEP at pH = 7.2.